Ultrasonic evaluation of silicon/adhesive/copper interfaces in IC packages - Abdul Jaleel B. Shahul Hamid (2008)
This thesis evaluated the quality of the silicon/die attach/copper leadframe interfaces by using normal incidence ultrasonic waves.